Comparative analysis of MVD and RHZ in the treatment of primary glossopharyngeal neuralgia: A clinical report on 61 cases - Wang, Leibo; Liu, Qingjun; Dong, Xiaoxia; Wang, Junwei (Frontiers in Neurology, 2023)
Objective: Clinical data of 61 patients (grouped by MVD and RHZ)with glossopharyngeal neuralgia were analyzed retrospectively. To summary analysis of glossopharyngeal neuralgia (GN) of effective rate and surgical complications. Method: 63 patients with GN were admitted to our hospital by the professional group of cranial nerve diseases. 2 of them with a final diagnosis of tongue cancer and upper esophageal cancer secondary to GN were excluded from the group. The remaining patients all met the diagnosis of GN, some of them were treated with MVD, and others were treated with RHZ. The pain relief rate, long-term results, and complications of the patients in two groups were well organized and analyzed. Result: Of the 61 patients, 39 were treated with the MVD and 22 were with RHZ. The efficiency of both groups was 100%. 1 case in the MVD group had a recurrence 4 years after surgery and was cut off again. Complications related to operation: 1 case of swallowing and coughing in the MVD group, 3 cases in the RHZ group; 2 cases of uvula not centering in the RHZ group; 2 cases in the RHZ group, 2/3 of the back of the tongue lost taste, most of them disappeared or decreased after follow-up. In terms of serious complications, there were 2 cases of postoperative bleeding in the MVD group. Based on the clinical characteristics of the patients' bleeding, it was judged that the cause of the bleeding was ischemic bleeding and was related to intraoperative injury to the penetrating artery of the PICA artery and vasospasm. Conclusion:We believed that for cases with complex vascular compression, tight vascular adhesions, difficult separation, and without clear vascular compression, the RHZ could be performed as appropriate, whose efficiency did not differ significantly from that of MVD, and there was no significant increase in complications such as cranial nerve disorders, but it helped to reduce the risk of ischemia and bleeding due to surgery by reducing the risk of arterial spasm and injury to the penetrating arteries due to separation of vessels during MVD. And the risk of recurrence was reduced.